2000
DOI: 10.1186/1471-2156-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus IE1 promoter/enhancer drives variable gene expression in all fiber types in transgenic mouse skeletal muscle

Abstract: Background: Versatile transgenic manipulation of skeletal muscle requires knowledge of the expression profiles of diverse promoter/enhancer elements in the transcriptionally specialized fiber types of which muscle is composed. "Universal" viral promoters/enhancers, e.g., cytomegalovirus IE1 (CMV IE1), are of interest as reagents that may drive broad expression. However, a previous study noted a marked heterogeneity of CMV IE1-driven transgene expression among muscle fibers, raising the possibility of fiber-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Interestingly, earlier studies featuring AAV9-CMV revealed higher rates of transduction of the TA muscle compared to SOL, suggesting that myofiber types may be differentially permissive to AAV-mediated transduction and transgene expression ( Bostick et al, 2007b ). Results from other previous studies suggest that CMV promoters do not discriminate between myofiber types, ( Hallauer and Hastings, 2000 ; Robinson et al, 2005 ) given that SOL muscle consists mainly of type 1 (slow-twitch) fibers, whereas TA, EDL, GA, and QUAD muscles include more type 2 (fast-twitch) fibers ( Komiya et al, 2017 ). Here, we observed that the fluorescence intensity and biodistribution of mCherry resulting from the IM inoculation of AAV8-LAP2 and AAV9-LAP2 drive robust transgene expression.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, earlier studies featuring AAV9-CMV revealed higher rates of transduction of the TA muscle compared to SOL, suggesting that myofiber types may be differentially permissive to AAV-mediated transduction and transgene expression ( Bostick et al, 2007b ). Results from other previous studies suggest that CMV promoters do not discriminate between myofiber types, ( Hallauer and Hastings, 2000 ; Robinson et al, 2005 ) given that SOL muscle consists mainly of type 1 (slow-twitch) fibers, whereas TA, EDL, GA, and QUAD muscles include more type 2 (fast-twitch) fibers ( Komiya et al, 2017 ). Here, we observed that the fluorescence intensity and biodistribution of mCherry resulting from the IM inoculation of AAV8-LAP2 and AAV9-LAP2 drive robust transgene expression.…”
Section: Discussionmentioning
confidence: 91%
“…EGFP gene detection was addressed for its wide use as marker of transgenosis event, both in in vitro and in vivo preclinic trials, and thus represents a well-known reporter system. On the other hand, studies on mice have demonstrated the importance of the CMV promoter in high level and constitutive gene expression, i.e., in skeletal muscle. , …”
Section: Resultsmentioning
confidence: 99%
“…In our cassette, GFP was expressed under CMV promoter; thus, we cannot exclude the possibility of suboptimal activity of CMV promoter in MyHC-2b myofibers. However, previous studies showed that the CMV promoter does not discriminate between myofiber types [ 28 , 29 ]. Additional studies with different promoters and reporters could clarify this potential concern.…”
Section: Discussionmentioning
confidence: 99%